(untitled) (Veterinary Science, 2019)
Although the expression Wnt and its isoforms are widely known in the embryonic skeletogenesis, little is known about the role they play in the particular Wnt3 isoform in the repair of orthopedic bone defects. Thirty rabbits were used, which were given a bone defect in one of the radiuses. The defect was refilled with demineralized bone matrix (DBM). The rabbits were sacrificed at 7, 15, 21, 30, 60 and 150 days post-treatment to immuno-detect the Wnt3 in the repair sites. The immuno-determination was done by optic density (OD) and integrated optic density (IOD). Both, the OD and the IOD were analyzed using ANOVA and Fisher LSD test. The Wnt3 protein was immuno-detected in mesenchymal cells, in the sites where the chondrogenesis was produced and in osteoprogenitor, preosteoblasts and osteoblasts cells. The OD had significant variations (p<0,05) at 7, 15, 60 and 150 days post-treatment. The same statistical analysis for IOD showed significant statistical differences (p<0,05) at day 30 with respect to 60 and 150 days post-treatment. The evidence showed the histological sites as well as the chronological immune expression of Wt3 in the repair of orthopaedic bone defects treated with demineralized bone matrix.